Resolubilidade da atenção primária à saúde: encaminhamentos para o serviço do setor secundário - Baptista, Claudio Ártico (2023)
Objective: To characterize Primary Health Care referrals and analyze their resolvability based on medical specialty referrals. Method: Analytical cross-sectional study with time series analysis based on data, which are based on document analysis of EMPRO system records and Open Court available in the municipality of São José do Rio Preto from 2015 to 2021. The variables referred to the number of medical consultations at the Basic Health Units (UBS) and consultations at the Specialty Medical Center (CME), in addition to the number of referrals recorded per health unit. Data were analyzed using descriptive statistics (mean, median, standard deviation, percentile, minimum and maximum value) for numeric variables and number and proportion for categorical variables. Statistical analysis was performed using Excel and IBM SPSS Statistics version 29 software; comprising three moments: Before the coronavirus pandemic and without a protocol for referrals (2015-2019); before the pandemic and with a protocol (2019 – March 2020); and during the pandemic and with a protocol (2020 – 2021). Subsequently, a time series analysis was carried out with the calculation of the Index generated through Seasonality. The resolvability indicator based on the parameter recommended by the National Program for the Improvement of Access and Quality of Primary Care (PMAQ) was also calculated. The study meets the ethical precepts and was approved by the FAMERP`s Research Ethics Committee (CEP). Results: A total of 3,697,779 consultations were obtained between the years 2015 to 2021 of primary care and of these, 2018 was the year with the highest number of medical consultations (15.9%), and the lowest in a period of 12 months, it was in 2020 (13.0%). The average number of visits ranged from 40,103.42 to 52,302.25. Regarding the referrals addressed, a total percentage of 19.7% in 2018, 29.6% in 2019, 14.0% in 2020 and 17.6% in 2021. The basic health units with the highest number of referrals ranged more of 7.5% between 2018 and 2019, and 7.0% between 2020 and 2021. It is worth mentioning a reduction in the number of referrals to primary health care. Attendances at the specialty medical center between 2018 and 2021 were 616,762. In addition, there was a variation in the number of referrals from Primary Health Care to the Specialty Medical Center. Conclusion: It is observed that Primary Care in the municipality of São José do Rio Preto was resolutive; except in 2019. This study has the impact of diagnosing the situation of primary care services that contribute to the planning and structuring of health services.